THE INFLUENCE OF PROFITABILITY, DEBT POLICY AND MANAJERIAL OWNERSHIP TO FIRM GROWTH OPPORTUNITY - Pratama, Rendy Gigih; Purwanti, Lilik (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study aims to examine the key factors affecting growth opportunity on manufacture companies which listed on Indonesia Stock Exchange. This study examined factors such as profitability, debt policy and manajerial ownership as their dependent variable and firm growth opportunity as dependent variable. Sample from this study consist of manufacture companies listed on the Indonesia Stock Exchange. The data used in this study is secondary data with sample selection using purposive sampling method. Analysis tools used in this study is multiple regression analysis with a significance level of 5%. The results of this studyÂ show profitability and dept policy have positive significant effect on firm growth oportunity. Manajerial ownership has negative significant effect on firm growth opportunity. Key words : profitability, debt policy, manajerial ownership, growth opportunity.